ZAKRES DOPUSZCZALNOŚCI POROZUMIEŃ W PROCESIE KARNYM - Struczyk, Edward (Zeszyty Prawnicze, 2017)
The Scope of Agreements’ Admissibility in Criminal Proceedings Summary The principle of investigation in the Polish criminal proceedings has consolidated The preparatory proceedings are even ruled thereby. The situation seems better in the stage of court proceedings. Nevertheless, contentiousness is still exceptional in criminal proceedings. This is going to be changed by agreements reached in the course of criminal proceedings. The agreements concluded in criminal proceedings are settlements between different parties of the same trial (horizontal agreements) or agreements between one party to the criminal proceedings and a judicial body conducting those proceedings (vertical agreements). The notion of ‘agreements’ in criminal proceedings m ust be understood widely. They are agreements which result from any possible activity o f the said subjects aimed at working out a com m on position in any matter of the proceedings, viz not only those aimed at settling issues of criminal liability and sanction (submission to penalty, conviction w ithout first-instance hearing, voluntary submission to criminalliability, mediation etc.) but also those concerned with incidental problems (safe-conduct, bails, im m unity witness etc.). These agreements can be divided into the following types: formal ones (resulting from rules o f practice), informal (resulting from rules o f substantive law) and para-formal (not specified in legal regulations). The model of an agreement in criminal proceedings originates from the consensual method of judgment penetrating into the continental system of law from the sphere of common law. This tendency shows a graduał withdrawal from the traditional retaliatory function of criminal proceedings in favour of compensation. The new possibilities are conducive both to the parties’ interests as well as the economics of the proceedings. Moreover, the agreements allow the State to gradually cease to dom inate in the sphere of criminal proceedings. Notwithstanding the above the agreements in question are still scarce in the hitherto formalized practice of criminal proceedings.